(untitled) (Journal of the College of Basic Education, 2022)
Uses human language speech and language expression pantomime (in the flesh), then there are two languages ​​for communication and contact no less important than the one on the other, and unable to him one complemented and تعضده second, and the body of an important role with the language of speech, or without, the most emotional and honest is the language of expression and gesture, the deepest expressions emotional reflected in performance art, E. y events that occurred, news and more appear in the expression of the most intense performance, and the language of performance disclose more quickly from one language to talk about insider a personal visual language. In our marked (b Instant symbolic spaces offer open) are trying to detection and identification for Instant symbolic spaces offer open as it represents a fundamental value related to communicate and receive via performance in the show open, and to achieve this art from a significant role in the social dimension and humanitarian generally As an important part of the general culture of the march through the building foundations qualify and highlight the process and a new world is open to multiple interpretations and readings, including the magnitude of the uncertainty and difficulty in understanding. Therefore, the researcher adopted the approach analytically through the description and analysis of the artwork across all its advantages, including is based on the work surface with all its terms of reference for the purpose of understanding the causes of the problem and ways to reduce them through what is achieved by us this search across all joints to brings us to achieve a thorough understanding of what is going on in the art performance through understanding the causes of these problematic and varying and arent the mechanics of interpretation and organized labor with those artifacts. In the first chapter, the researcher sought to display the search problem to determine the importance of research and the approach it and then determine the objective of this research is the symbolic Instant detection in open spaces offer (the art of performance model). It is during the second trimester researcher focused on the symbol and its role in the art of performance and on the meaning of the symbol and its importance in the open display spaces in performance art And took the researcher during the third quarter trend analysis of works of art to the artists الادائيين in spaces offer open and mechanism اشتغالهم which included identifying the research community and appointed by the (3) samples chosen by the researcher is my intention through the procedures and rationale to set off towards the method of analysis through descriptive analytical method. In the fourth quarter results were discussed and through what has resulted analytical study researcher concluded a set of results for the performative art and symbolic dimensions and is the most important of the following: 1 - The confluence of the structure show open in the art of performance symbol to confer on display values ​​semantic and expressive, making it open to the readings multi Hence the importance of the icon in the artwork and display both as in the sample (1) and (2) as Abadahma for direct and يكسبهما seems to offer immunity as a result of performance piece to celebrate the symbolic cause for strange and causing shock and amazement who Ichdan receiver to the offer Viamq to contact him. 2 - in the sample (1) and (3) that the messaging icons RDM in performative supply formats makes the mind of the receiver configured to reflect and absorb the same icons and implications and then interpreted, and the receiver then becomes a key element in the production of meanings rather than a passive recipient. 3 - manifested Instant Code as a dominant support other marks RDM in performative supply structure block because of it Alamih give the display attributes surprising and meditation continues receiver with the artist in the eye (1), (2), (3). 4 - The symbol represents a compromise bearer of the contents and the visions teeming open display in the art of performance hence the importance and usefulness as in the sample (1).